Testing psychometric property on the Indonesian Academic Self-Efficacy Scale (TIASS) - Darmayanti, Kusumasari Kartika Hima; Meyrinda, Jesyia; Anggraini, Erlina; Utami, Annisa Nurul; Martha, Ati Suci Dian; Faizah, Lailatul; Maulina, Dewi; Seniati, Ali Nina Liche (Jurnal Psikologi, 2024)
Background: First-year undergraduate students face the learning style transition in high schools and universities and struggle to accept a new academic environment. Previous studies found that academic self-efficacy is important in predicting academic achievement among first-year undergraduate students. However, no specific instruments were developed in the Indonesian context. Purpose: This research aimed to develop and test the psychometric properties of The Indonesian Academic Self-Efficacy Scale (TIASS). Method: The scale was developed using Zajacova’s theory on academic self-efficacy. The test tryout involved 251 first-year college students, both female and male, aged 18-22 (M = 19.56, SD = 2.47). Statistical analysis used classical test theory and the Rasch model. Reliability was assessed with Stratified Alpha, Cronbach's Alpha, and the Rasch Model, while validity was evaluated through construct and concurrent validity.Findings: The final 20 items effectively measure academic self-efficacy in first-year undergraduates, demonstrating good reliability (Cronbach’s Alpha = .692-.781, Stratified Alpha = .902, Item Separation Reliability = .990, and Person Separation Reliability = .880) and validity (t-value range from 9.779 to 36.323 and λ ranged from -.070 to .774).Implication: TIASS is a reliable and valid scale for assessing academic self-efficacy, providing a baseline for designing interventions to boost first-year student’s academic confidence.